Process Evaluation of an Intervention Program to Reduce Occupational Quartz Exposure Among Dutch Construction Workers. Issue 4 (April 2015) - van Deurssen, Erik H. A. M.; Pronk, Anjoeka; Meijster, Tim; Tielemans, Erik; Heederik, Dick; Oude Hengel, Karen M.
Abstract : Objectives: Evaluate the process of an intervention in the construction industry to reduce quartz exposure. Methods: In a cluster randomized controlled trial, data on seven process aspects (ie, recruitment, reach, dose delivered, dose received, fidelity, satisfaction, and context) were quantitatively collected on manager and worker levels. Results: Dose delivered was 95% for the plenary sessions and 20% for the worksite visit. Although the protocol was mostly implemented as intended, dose received was lower than expected. Both managers and workers appreciated the intervention and recommended the intervention for future implementation. Workers attending all intervention sessions were most satisfied about the intervention. Conclusions: High rates for dose delivered and fidelity for the plenary sessions and relatively high satisfaction rates were achieved. Furthermore, continuous monitoring of contextual factors beforehand and alongside the implementation of interventions is recommended.